An Effective Predictive Analysis Model using Logistic Regression - P.Chandramoorthi (International Journal of Engineering and Management Research, 2020)
Logistic Regression is used to predict a dependent variable, given a set of independent variables, such that the dependent variable is categorical. Logistic regression analysis is the most frequently used of all statistical techniques. This paper explains the basic concepts and explains the concept of Logistic Regression in prediction Analysis.